1997
DOI: 10.1007/s002130050175
|View full text |Cite
|
Sign up to set email alerts
|

Ontogeny of dopamine agonist-induced sensitization: role of NMDA receptors

Abstract: In contrast to adults, preweanling rats exhibit behavioral sensitization for only a few days after cessation of dopamine (DA) agonist treatment. The reasons for this ontogenetic difference are uncertain, but maturational changes in the N-methyl-D-aspartate (NMDA) receptor may be responsible, since stimulation of these receptors is necessary for the development of DA agonist-induced sensitization in adult rats. The purpose of the present study was to examine the relationship between NMDA receptor functioning an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 36 publications
2
30
0
1
Order By: Relevance
“…Most studies on behavioral sensitization to psychostimulants are performed on adult rats, although there are reports that demonstrate young rats also show sensitized behavioral responses to amphetamine (McDougall et al, 1994;Duke et al, 1997). Prior to initiating physiological investigations of glutamatergic synapses, we wanted to confirm that the young rats used in our physiological experiments exhibit a sensitized response to amphetamine.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies on behavioral sensitization to psychostimulants are performed on adult rats, although there are reports that demonstrate young rats also show sensitized behavioral responses to amphetamine (McDougall et al, 1994;Duke et al, 1997). Prior to initiating physiological investigations of glutamatergic synapses, we wanted to confirm that the young rats used in our physiological experiments exhibit a sensitized response to amphetamine.…”
Section: Resultsmentioning
confidence: 99%
“…Various factors might be responsible for this ontogenetic difference in behavioral sensitization, including drug pharmacokinetics, age-dependent differences in dopamine and glutamate neuronal systems, and changes in associative learning abilities. Although an obvious possibility, there is little evidence suggesting that ontogenetic changes in dopaminergic and glutamatergic systems are responsible for age-dependent differences in behavioral sensitization (Duke et al 1997). For example, by 15 days of age, striatal dopamine (D 1 -like and D 2 -like) and glutamate [N-methyl-D-aspartate (NMDA) and non-NMDA] receptor levels have reached adult values (Gelbard et al 1989;Insel et al 1990;Miller et al 1990;Rao et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, young rats do not appear to show adult-like behavioral sensitization. More specifically, young rats will exhibit a sensitized response after one or two abstinence days (McDougall et al 1994;Bowman et al 1997;Duke et al 1997;Tirelli and Ferrara 1997;Wood et al 1998); however, behavioral sensitization is typically not observed after a more extended abstinence period (Fujiwara et al 1987;Kolta et al 1990;McDougall et al 1994;Ujike et al 1995). Two exceptions to this pattern of results have been reported, as young rats given repeated injections of a high dose of methylphenidate (20 mg/kg) exhibited long-term maintenance of a sensitized sniffing response (McDougall et al 1999).…”
Section: Introductionmentioning
confidence: 89%
“…It has been reported that moderate doses of MK801 (but not higher doses) prevent D1 dopamine receptor supersensitivity [45] and dopamine release [1] . Furthermore, behavioral sensitization induced by dopaminergic agonists may be prevented by moderate doses of MK801 [46] . Interestingly, the dopaminergic system also regulates NMDA receptor function.…”
Section: Discussionmentioning
confidence: 99%